Predicting Late Recurrence of Atrial Fibrillation After Radiofrequency Ablation in Patients With Atrial Fibrillation: Comparison of C2HEST and HATCH Scores - Han, Jingjing; Li, Guangling; Zhang, Demei; Wang, Xiaomei; Guo, Xueya (Frontiers in Cardiovascular Medicine, 2022)
Objective: We want to investigate the risk of recurrence in patients with atrial fibrillation after radiofrequency ablation and predict it using C2HEST and HATCH scores. Method: We retrospectively included 322 patients with atrial fibrillation, and the final 261 patients were included in the analysis. They had atrial fibrillation and were admitted for radiofrequency catheter ablation. We compared the ability of C2HEST and HATCH scores to predict recurrence after radiofrequency ablation of atrial fibrillation. The predictive ability of C2HEST and HATCH scores for atrial fibrillation recurrence was estimated by the area under the receiver operating characteristic curve. The difference in receiver operating characteristic curve between the two models was compared using the DeLong test. Results: Of the 261 patients included in the analysis, 83 (31.6%) patients experienced a late recurrence of atrial fibrillation after radiofrequency ablation. The risk of postoperative recurrence of atrial fibrillation increased with increasing C2HEST and HATCH scores. The area under the receiver operating characteristic curve of C2HEST and HATCH scores in predicting postoperative recurrence of atrial fibrillation was 0.733 (95%CI, 0.713-0.833) and 0.801(95% CI, 0.740-0.861), respectively. There was no significant difference between the two models in their ability to evaluate patients for postoperative recurrence of atrial fibrillation (DeLong test p-value = 0.36). Among the risk factors in both models, hypertension and heart failure contributed the most to postoperative recurrence after atrial fibrillation, and higher blood pressure and lower cardiac ejection fraction were associated with a higher risk of recurrence. Conclusion: Both C2HEST and HATCH scores were significantly associated with the risk of late recurrence after radiofrequency ablation of atrial fibrillation. There was no significant difference in predictive power between the two models. Keywords: atrial fibrillation, radiofrequency ablation, hypertension, heart failure, C2HEST scores, HATCH scores